Cost of Healthcare-associated Infections Developing After Endourologic Surgery and the Efficacy of Control Measures in a Turkish University Hospital - Mehmet Enes Gökler; Burhanettin Işıklı; Barbaros Başeskioğlu (Journal of Urological Surgery)

(untitled)
Objective:The study aimed to determine additional costs of healthcare-associated infections (HAIs) in patients undergoing endourologic surgery. It also aimed to evaluate the effect of infection control measures on costs of HAIs.Materials and Methods:This interventional study carried out in patients admitted to the Department of Urology at Osmangazi University Hospital between January 2014 and October 2015. All surgeries were examined in the pre-intervention period for six months and then, a prevention package and education period, which intended to reduce hospital infections, were implemented. In the post-intervention period, all endourological operations were examined for 2 months.Results:The prevalence of HAIs in the pre-intervention and post-intervention periods was 10.1% and 4.9%, respectively. Patients who had healthcare-related infections before or after the intervention had higher costs compared to those who did not get infections. It was found that HAIs decreased by 51% after the intervention (relative risk: 0.49, 95% confidence interval: 0.28-0.86). Thus, an additional cost of 146.332.8±139.29 TL was saved.Conclusion:It is concluded that monitoring and reporting of HAIs regularly by using a simple but effective and evidence-based infection control practices and education programs could decrease the frequency of infection, high additional costs and length of hospital stay.